A Content Analysis of Infant and Toddler Food Advertisements in Taiwanese Popular Pregnancy and Early Parenting Magazines. (August 2015) - Chen, Yi-Chun; Chang, Jung-Su; Gong, Yu-Tang
Background: Mothers who are exposed to formula advertisements (ads) are less likely to initiate breastfeeding and more likely to breastfeed for a shorter duration than other mothers. Objective: The purpose of this study was to examine infant and toddler food ads in pregnancy and early parenting magazines. Methods: A content analysis of infant and toddler food ads printed in 12 issues of 4 magazines published in 2011 was performed. Coding categories of ads included product category, advertisement category, marketing information, and advertising appeal. The target age and health-related message of each product were coded. Results: The researchers identified 756 infant and toddler food ads in the magazines. Compared with complementary food ads, formula product ads used more marketing strategies such as antenatal classes and baby contests to influence consumers and promote products. Nutritional quality and child health benefits were the two most frequently used advertising appeals. In addition, this study identified 794 formula products and 400 complementary food products; 42.8% of the complementary food products were intended for 4-month-old infants. Furthermore, 91.9% of the ads for formula products and 81% of the ads for complementary food products contained claims concerning health function or nutrient content. Conclusions: Taiwanese pregnancy and early parenting magazines contain numerous infant and toddler food ads. These ads generally use health-related claims regarding specific nutrient content and health functions to promote infant and toddler foods. Health professionals should provide more information to parents on the differences between breast milk and formula milk, and they should be aware of the potential effect of infant and toddler food ads on parents' infant feeding decisions.